Localization and specificity of binding of subprimate placental lactogen in rabbit tissues. - Bolander, F F (1976)
A search for specific placental lactogen binding was undertaken in tissues obtained from late pregnant rabbits using the placental lactogens from sheep, cows, and human beings. 125I-labeled ovine lactogen exhibited highest specific binding to the adrenal gland (57.8%), followed by liver (21.5%), ovary (19.9%), mammary gland (15.9%), uterus (12.2%), kidney (8.8%), brain (8.5%), and adipose tissue (7.9%). In liver and mammary gland, the displacement curves for ovine and human lactogen were identical to that for bovine prolactin, indicating that they share the same receptor site. Although the displacement curve for bovine lactogen was parallel to that of the other lactogens the bovine hormone is less active in the radioreceptor assay.